KEBIJAKAN PENGELOLAAN HUTAN, KEMISKINAN STRUKTURAL DAN PERLAWANAN MASYARAKAT - Deddy Winarwan (Jurnal Kawistara, 2011)
The government's implementation of various forest management policies often fails to protect forest and reduce the number of poor communities around it. This study aims to discover disctimination in forest management oplicies issued and implementation by the State, the erultant structural proverty, and social resistance from by communities within and around forest conservation areas. this study was a qualitative one using a descriptive analytical approach conducted at the State level, Husserl's phenomenology at an individual level and Berger at collective level. The location of the result of the study indicate that the logging done by the local community was due to their displeasure with the goverment's policies, considered discriminatory in their application to the timber company and community. Implementation of deliberative policy to resolve conflicts between the government and Atar Lebar community int the TNBBS forest conservation area is necessary for the resolution of the socio-structural problems in Atar Lebar